2001
DOI: 10.1016/s0300-483x(00)00458-3
|View full text |Cite
|
Sign up to set email alerts
|

A concise review of the toxicity and carcinogenicity of dimethylarsinic acid

Abstract: Dimethylarsinic acid (DMA) has been used as a herbicide (cacodylic acid) and is the major metabolite formed after exposure to tri-(arsenite) or pentavalent (arsenate) inorganic arsenic (iAs) via ingestion or inhalation in both humans and rodents. Once viewed simply as a detoxification product of iAs, evidence has accumulated in recent years indicating that DMA itself has unique toxic properties. DMA induces an organ-specific lesion -single strand breaks in DNA -in the lungs of both mice and rats and in human l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
98
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(100 citation statements)
references
References 47 publications
0
98
1
1
Order By: Relevance
“…Indeed, we observed that caveolin overexpression is associated with elevated forkhead phosphorylation (data not shown). Given that arsenite's toxic effects are mediated in large part through oxidative stress (14), this could be an important factor in the increased susceptibility of caveolin-overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we observed that caveolin overexpression is associated with elevated forkhead phosphorylation (data not shown). Given that arsenite's toxic effects are mediated in large part through oxidative stress (14), this could be an important factor in the increased susceptibility of caveolin-overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have examined the influence of caveolin expression on the cellular response to treatment with the tumor promoter arsenite (4,5,14). Our results indicate that caveolin overexpression leads to an increase in Akt activation, possibly through the diminished synthesis of ceramide, a lipid that was previously shown to inhibit PI3K activity (43).…”
mentioning
confidence: 86%
“…Genotoxicity of arsenic species does not involve direct interaction with DNA. It has been suggested that indirect processes such as oxidative damage evoked by reactive oxygen species (Basu et al, 2001;Gebel, 2001;Kenyon and Hughes, 2001;Liu et al, 2001Liu et al, , 2005Ahmad et al, 2002;Nesnow et al, 2002;Kitchin and Ahmad, 2003;) and the inhibition of DNA repair (Hughes, 2002;Rossman, 2003;Schwerdtle et al, 2003a) are implicated.…”
mentioning
confidence: 99%
“…Humans are exposed primarily to trivalent [arsenite, As(III)] and pentavalent [arsenate, As(V)] inorganic arsenicals present in the environment, as well as to organic arsenic [e.g., dimethylarsinic acid, DMA(V)] in some situations (Kenyon and Hughes 2001;Shen et al 2003b). In mammals, As(V) is first reduced to As(III), whereas As(III), produced by this reduction or from direct ingestion, is methylated primarily to pentavalent organic arsenicals including monomethylarsonic acid [MMA(V)] and DMA(V)].…”
mentioning
confidence: 99%